2017
DOI: 10.1021/acschembio.7b00062
|View full text |Cite
|
Sign up to set email alerts
|

Price for Opening the Transient Specificity Pocket in Human Aldose Reductase upon Ligand Binding: Structural, Thermodynamic, Kinetic, and Computational Analysis

Abstract: Insights into the thermodynamic and kinetic signature of the transient opening of a protein-binding pocket resulting from accommodation of suitable substituents attached to a given parent ligand scaffold are presented. As a target, we selected human aldose reductase, an enzyme involved in the development of late-stage diabetic complications. To recognize a large scope of substrate molecules, this reductase opens a transient specificity pocket. The pocket-opening step was studied by X-ray crystallography, micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(64 citation statements)
references
References 66 publications
(107 reference statements)
4
59
0
1
Order By: Relevance
“…In a recent joint experimental/computational study, Rechlin et al investigated the binding of a series of 2-carbamoyl-phenyloxy acetic acid derivatives to Human Aldose Reductase and found that the opening of a specific cleft in the binding pocket was dependent on ligand substituent due to protein reorganization and the ligand desolvation penalties. 69 MD simulations of the unbound protein found that the open conformation of this pocket was unstable relative to the closed conformation and solvation thermodynamic analysis confirmed the presence of energetically unfavorable water molecules inside the binding cleft. In another joint experimental and computational study, Maeno et al noted the existence of two states for the L99A mutant of T4 Lysozyme under high pressure conditions: a ground state with an enlarged hydrophobic cavity and a high energy state where a phenylalanine was flipped inside the cavity.…”
Section: Discussionmentioning
confidence: 91%
“…In a recent joint experimental/computational study, Rechlin et al investigated the binding of a series of 2-carbamoyl-phenyloxy acetic acid derivatives to Human Aldose Reductase and found that the opening of a specific cleft in the binding pocket was dependent on ligand substituent due to protein reorganization and the ligand desolvation penalties. 69 MD simulations of the unbound protein found that the open conformation of this pocket was unstable relative to the closed conformation and solvation thermodynamic analysis confirmed the presence of energetically unfavorable water molecules inside the binding cleft. In another joint experimental and computational study, Maeno et al noted the existence of two states for the L99A mutant of T4 Lysozyme under high pressure conditions: a ground state with an enlarged hydrophobic cavity and a high energy state where a phenylalanine was flipped inside the cavity.…”
Section: Discussionmentioning
confidence: 91%
“…Yet, the inhibitors 3 and 4 as well as 5 and 6 are similar, especially with regard to their Gibbs free energy of binding. [4]. All measurements were performed in HEPES buffer pH 8.0 and are not corrected for overlaying protonation effects, thus only relative differences should be interpreted.…”
Section: Thermodynamic Datamentioning
confidence: 99%
“…Remarkably, the carboxylate group at the acetic acid moiety of inhibitor 2 binds with only one well-defined orientation in the anion binding pocket. [4] in light green (A,B) and 2 (4QBX) [4] in dark green (C,D) bound to the active site of ALR-2. To distinguish the position of both conformations, b is highlighted by a slightly darker color.…”
Section: Comparison Of the Binding Poses Of Inhibitors 1-6mentioning
confidence: 99%
“…Extensive information is available in the literature about the structure and function of hAR, mainly related to active site of hAR from high-resolution crystal structures with a number of potential inhibitors 5 , flexibility in the hAR binding site pocket 6 and the thermodynamics of closing/opening of the specificity pocket within binding site pocket of hAR 7 . There is little investigation related to the folding/unfolding mechanism of hAR.…”
Section: Introductionmentioning
confidence: 99%